40 participants joined UMP Expedition in forging closer ties with Sabahans - UMP, PNC
A total of 40 people comprising staff and undergraduates of Universiti Malaysia Pahang (UMP) who were also members of an expedition that scaled Mount Kinabalu took the opportunity to get to know the locals in Kampung Lembah Permai, Kundasang in Ranau, Sabah.